Duże Skręcanie Bisymetrycznego Pręta Cienkościennego o Zmiennym Przekroju Dwuteowym - Wilde, P.; Wekezer, J. (Engineering Transactions, 1973)
In the paper discussed is the state of strain and stress in a bar with a bisymmetrical, variable I cross-section subjected to a finite twist. The deformation is described by the angle of twist and by the longitudinal deformation. The simplifying assumptions of the theory of thin-walled fundamental equations of finite torsion are obtained. The equations are derived from the equilibrium conditions from the principle of minimum potential energy by means of the variational calculus. The comparison of results enables the discussion of the physical meaning of the simplifications assumed.